Work-life Balance and Worker Well-being through Family Support - Hariani, Mila; Mardikaningsih, Rahayu (Journal of Social Science Studies, 2023)
Family support is important in improving the job quality and worker well-being. This article examines how emotional, practical and social support from family can influence workers’ mental well-being and their performance at work. Good family support can reduce stress, increase motivation, and create a balance between personal and work life, which has a positive impact on workers’ productivity. An imbalance in family support or conflict can lead to increased stress and decreased work quality. Social and cultural factors also influence how family support is received and have an effect on worker well-being. This article also suggests that organizations adopt policies that support work-life balance, such as flexible working hours and family time, and provide social support for workers who do not have immediate family. Such policies can improve worker well-being, reduce stress, and subsequently improve job performance and satisfaction.